The effect of albumin and cholesterol on the biotribological behavior of hydrogels for contact lenses - Silva, D. (2017)
Submitted by Paula Saraiva (psaraiva@egasmoniz.edu.pt) on 2017-06-07T10:04:27Z No. of bitstreams: 1 Artigo10_APSerro.pdf: 1821808 bytes, checksum: 20805584c6169804653756c5f28042ff (MD5)